The use of audiovisual material and its influence in the english vocabulary learning in second grade students, school year 2018-2019 - Carranza Ordoñez, Evelyn Elena (2020)
This paper aims to show the effective use of audiovisual material and its influence on the English vocabulary learning in second grade students at Academia Naval Guayaquil. For that purpose, a representative sample of Primary school students was selected. In the first stage of the study a questionnaire was applied to the English teacher to know the methodology of teaching vocabulary and different resources that help to develop it……..